Triumph of desire : Danish and international surrealism - Gether, Christian; Laurberg, Marie; Rugaard Jorgensen, Dorthe; Arken Museum for Moderne Kunst, Ishoj (Ishoj : Arken Museum for Moderne Kunst Ishoj, 2008)
Dali, Salvador ; Carlsson, Harry ; Bjerke-Petersen, Vilhelm ; Ernst, Max ; Kernn-Larsen, Rita ; Freddie, Wilhelm ; Miro, Joan ; Tanguy, Yves ; Masson, Andre ; Breton, André ; Aragon, Louis ; Muzard, Suzanne ; Unik, Pierre ; Mortensen, Richard ; Arp, Hans (Jean) ; Magritte, René ; Ferlov, Sonja ; Bille, Ejler ; Ubac, Raoul ; Heerup, Henry ; Carlsson, Harry ; Man Ray ; Hugnet, Georges ; Bellmer, Hans ; Brauner, Victor ; Jorn, Asger ; Miro, Joan ; Masson, Andre ; Heerup, Henry ; Pedersen, Carl-Henning ; Jacobsen, Egill ; Brassaï ; Clausen, Franziska ; de Sala, Eugène
Bibliog. p. 105
Publication in connection with the exhibition 'Triumph of desire: Danish and international surrealism' at the Arken Museum for Moderne Kunst in Ishoj, 06.09.2008-11.01.2009
boek